Answer:
f=1
Step-by-step explanation:
Let start off with doing -f plus 4f which gives you 3f. The equation would now be 2+3f=8-3f. Add 3f so you can cancel out the -3f and add the 3f to the other 3f. Now your equation is 2+6f=8. Cancel out do by doing -2. (Don't forget to to it to the 8 also.) Now your equation is 6f=6. Divide 6 from both sides to get 1. (You divide because you want to get f alone.
Answer:
-17x is the answer mark me brainliest
9 stacks of cards and 4 cards left over because when you divide 85 by 9 you get 9.4. So you'd multiply just 9 to get 81 and 4 cards leftover
♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️
![( 3 {x}^{2} - 13x - 10 ) \div (x - 5) = \\](https://tex.z-dn.net/?f=%28%203%20%7Bx%7D%5E%7B2%7D%20%20-%2013x%20-%2010%20%29%20%5Cdiv%20%28x%20-%205%29%20%3D%20%20%5C%5C%20)
![\frac{3 {x}^{2} - 13x - 10 }{x - 5} = \\](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%20%7Bx%7D%5E%7B2%7D%20-%2013x%20-%2010%20%7D%7Bx%20-%205%7D%20%20%3D%20%20%5C%5C%20)
![\frac{(x - 5)(3x + 2)}{(x - 5)} = \\](https://tex.z-dn.net/?f=%20%5Cfrac%7B%28x%20-%205%29%283x%20%2B%202%29%7D%7B%28x%20-%205%29%7D%20%20%3D%20%20%5C%5C%20)
![3x + 2](https://tex.z-dn.net/?f=3x%20%2B%202)
♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️